Discovering Best Practice for Establishing Evacuation Centers for Vulnerable Populations: Findings from an Australian Pilot Study. Issue Volume 34:Issue s1(2019) (May 2019) - Kako, Mayumi; Steenkamp, Malinda; Ryan, Benjamin; Arbon, Paul; Takada, Yosuke
Abstract : Introduction: Potentially vulnerable population groups in disasters include the elderly and frail, people who are isolated, and those with chronic diseases, including mental health conditions or mobility issues. The 2011 Queensland flood disaster affected central and southeast Queensland, resulting in 2.5 million people being adversely affected. Seventy-two local government areas disaster were activated under the Natural Disaster Relief and Recovery Arrangements, which was more than 99 percent of Queensland. The issues regarding the role and responsibility across governments relating to planning, setup, and management of evacuation centers will be discussed. Aim: This paper will report the preliminary findings of a pilot study undertaken with local government officials and humanitarian agencies in Australia concerning their involvement in planning for, setting up, and managing evacuation centers for vulnerable populations in Australia during the Queensland floods in 2011. The objective is to illuminate the challenges officials faced, and the resolutions and lessons learned in the preparation of evacuation centers through this event. Methods: The study involved interviews with local government and relevant agencies' officials who have been involved in establishing evacuation centers for vulnerable populations during the 2011 floods. Six officials were recruited from local government areas affected by the disaster in Queensland, Australia. Semi-structured phone interviews were audio-recorded and thematic analysis was conducted using NVivo software. Results: Three core themes emerged: 1) understanding of the importance of preparation, 2) challenging evacuation center environments, and 3) awareness of good governance principles. Discussion: This pilot study demonstrated that communication with stakeholders during the preparation period prior to a disaster is essential to best practice for evacuation center management. Understanding and being aware of good governance is also an important element to establish evacuation centers effectively.